Computational studies of Vitexin isolated from Vitex negundo against Rheumatoid Arthritis targets (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
One of the chronic inflammatory autoimmune diseases that need attention to be treated is Rheumatoid arthritis. Especially RA encounters more female cases manifests progressive destruction of bone and cartilage. Expression of more inflammatory cytokines and Matrix Metallo-Proteins at the synovial tissue destruct collagen structure and worsen the condition. Generally anti-inflammatory drugs and immune-modulatory agents are used to deduce the progression of disease. Such chemical entities have proven many side effects and expensive. This study provides a glimpse of structural based drug designing using bioactive pharmakon from a folk chloric herb. Vitex negundo is a traditionally available plant that has been reported to possess pharmaco-beneficiary bioactive flavonoids especially, vitexin. Virtual screening involves docking of vitexin with three different targets that is responsible for triggering collagenase enzyme was achieved using Autodock. Binding energy of vitexin and TNF α receptor1(TNFR1) was found to be slightly higher when compared to docking results of TNF α converting enzyme (TACE) and Human Inhibitory Kinase β (hIKβ) proteins. The molecular interactions were visualized using BIOVIA discovery studio visualizer. This study may evident that vitexin has enhanced pharmacological benefits that need to be ensured through in vitro and in vivo assays.